Penerapan Analisis Swot Sebagai Strategi Untuk Meningkatkan Payment Collection (Studi Kasus Pada Pt Zenith Utama Mandiri ) - Sihombing, Marusaha O; Nawaningtyas P, Nur (Jurnal Sains dan Teknologi (JSIT), 2024)
This study aims to explore the application of SWOT analysis as a strategy to improve the effectiveness of payment collection at PT Zenith Utama Mandiri. In a competitive business environment, efficient payment management is crucial for the continuity of cash flow and financial stability of the company. This study uses a qualitative descriptive method using primary data, data collection is obtained from field observations, interviews and questionnaires and analysis using the SWOT framework (Strengths, Weaknesses, Opportunities, Threats) to identify factors that affect collection performance, both from internal and external aspects. In this study, the sample used was 13 employees of PT Zenith Utama Mandiri. The results of the study indicate that internal factors (such as management support and technology systems) and external factors (such as economic conditions and customer behavior) significantly affect the success of the collection process. The application of a SWOT-based strategy provides PT Zenith with clarity in developing steps to improve cash flow and collection efficiency, including improving training, strengthening technology systems, and adaptive communication strategies. In conclusion, SWOT analysis can be used as an effective strategic tool to strengthen the payment collection process and reduce the company's financial risk.